An Evaluation of Dam Removal Policy and Practices In The Nature Conservancy's Eastern Region. - Zinder, Daniel.; von Trapp, Kiersten.; Soule, Jessica.; Bird, Jasmine. (Tufts University. Tisch Library., 2018)
2009 M.A. in Urban and Environmental Policy and Planning Field Project. Client: The Nature Conservancy.